The Jargons Used in Police Activities - Lestari Dewi, Ni Putu Juliani; Anabokay, Yanrini Martha; Ndun, Yandri Susuek (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
This writing tries to identify the kinds of jargons used in police activities. This research was a descriptive qualitative and this research was design to find out the kind of jargon, to analyze the meaning and describe the intended of the jargon used in police activities. There were two methods in collecting the data, they were observation and interview. The result shows that there were three kinds of jargon used in police activities, namely: letter code, number code and corps institutions code and the jargon in police field is a code. Those also have their meaning to make listener easier to understood and intended to make and to keep communication short, easier in delivering the information and also make the intend to keep the secret of the language and the identify of policemen in doing their activities every day.